1998
DOI: 10.1161/01.atv.18.10.1662
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin C Protects Human Arterial Smooth Muscle Cells Against Atherogenic Lipoproteins

Abstract: Abstract-Glutathione (GSH) plays a key role in cellular antioxidant defenses by scavenging reactive oxygen species and reducing lipid peroxides. Intracellular GSH levels are regulated by transport of its precursor L-cystine via system x c Ϫ , which can be induced by oxidant stress. As oxidatively modified low density lipoproteins (LDLs) contribute to impaired vascular reactivity and the formation of atherosclerotic lesions, we have examined the effects of oxidized LDL and the antioxidant vitamins C and E on th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
16
2

Year Published

1999
1999
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(18 citation statements)
references
References 65 publications
0
16
2
Order By: Relevance
“…The data indicate that apoptosis might be induced by TNF-K, as the release of DNA fragments and histones is the key feature in apoptosis [15]. The death in VSMCs by oxidized low density lipoprotein and cytokines was blocked by ascorbic acid [16] and nitrogen oxide synthase inhibitor [5], respectively. Thus, it was investigated whether TNF-K-induced apoptosis was in£uenced by ascorbic acid or N G -monomethyl-L-arginine (L-NMMA) (Fig.…”
Section: Death In Vsmcs By Tnf-k Is Induced In the Presence Ofmentioning
confidence: 95%
“…The data indicate that apoptosis might be induced by TNF-K, as the release of DNA fragments and histones is the key feature in apoptosis [15]. The death in VSMCs by oxidized low density lipoprotein and cytokines was blocked by ascorbic acid [16] and nitrogen oxide synthase inhibitor [5], respectively. Thus, it was investigated whether TNF-K-induced apoptosis was in£uenced by ascorbic acid or N G -monomethyl-L-arginine (L-NMMA) (Fig.…”
Section: Death In Vsmcs By Tnf-k Is Induced In the Presence Ofmentioning
confidence: 95%
“…Indeed, oxidised LDL is known to be cytotoxic to a variety of cell types including endothelial cells, smooth muscle cells, macrophages and lymphocytes [9][10][11][12][13]. We have shown using LDL oxidised to defined extents that LDL containing the maximum level of lipid hydroperoxides (LOOH), termed moderately-oxidised LDL, can induce apoptosis in human umbilical artery smooth muscle cells, whereas native LDL does not [14]. However, we now demonstrate that although moderately-oxidised LDL induced apoptosis in macrophages, the LDL species most toxic towards this cell type is a highly-oxidised LDL preparation, rich in 7-ketocholesterol.…”
Section: Introductionmentioning
confidence: 99%
“…Some epidemiological studies in man [20,21], but not all [22], have shown that individuals who consume high concentrations of ascorbate through diet or supplements tend to have lower risks of cardiovascular disease, however, large clinical trials have found no benefits of antioxidant supplementation on cardiovascular disease risk [23]. We and others have shown that antioxidants [24,25], including ascorbate [14], afford protection to cells from the pro-apoptotic effects of oxidised LDL. This phenomenon has also been observed in macrophages [26,27].…”
Section: Introductionmentioning
confidence: 99%
“…Our studies in human cultured umbilical artery smooth muscle cells (HUASMCs) have shown that oxidized LDLs, but not native or mildly oxidized LDLs, induce time-and concentration-dependent (10-100 j.lg (ml proteinfl) adaptive increases in intracellular GSH levels and the activity of the anionic amino acid transporter system x c -(mediates entry of the GSH precursor cystine), which were dependent on protein synthesis and the extent of LDL oxidation (Siow et al 1998). Moreover, pretreatment of HUASMCs for 24 h with vitamin C (20-100 j.lM) depressed basal and abolished oxidized LDL-induced increases in GSH and system x c -transport activity.…”
mentioning
confidence: 91%
“…The glutathione (GSH) redox cycle forms a primary defence against oxidative insult and is induced in endothelial, smooth muscle and macrophage cell types by oxidative stress agents including oxidatively modified low density lipoproteins (LDLs) (Siow et al 1998). The gaseous monoxides nitric oxide (NO) and carbon monoxide (CO) have been identified as important cellular messengers involved in the regulation of vascular smooth muscle tone (Moncada et al 1991 ;Maines, 1997), and increased expression of inducible isoforms of nitric oxide synthase (iNOS) and haeme oxygenase (HO-1) have been detected in human atherosclerotic lesions (Butteryet al1996;Wilcox et a1.1997;Wang et al1998).…”
mentioning
confidence: 99%